2015
DOI: 10.1007/s12039-015-0815-0
|View full text |Cite
|
Sign up to set email alerts
|

Polypyridyl iron(II) complexes showing remarkable photocytotoxicity in visible light

Abstract: Iron(II) complexes of polypyridyl ligands (B), viz. [Fe(B) 2 ]Cl 2 (1 and 2) of N, N, N-donor 2-(2-pyridyl)-1,10-phenanthroline (pyphen in 1) and 3-(pyridin-2-yl)dipyrido[3,2-a:2',3'-c]phenazine (pydppz in 2), are prepared and characterized. They are 1:2 electrolytes in aqueous DMF. The diamagnetic complexes exhibit metal to ligand charge transfer band near 570 nm in DMF. The complexes are avid binders to calf thymus DNA giving binding constant (K b ) values of ∼10 6 M −1 suggesting significant intercalative D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The LD50 values for complex 1 in HeLa cells are 0.2 μM with light and 1.6 μM without, giving a photo-index of 8. It is worth noting that while other compounds have been shown to have values of up to 3 magnitudes higher 22 23 , many other small metal complexes are reported with similar photo-indexes of <10 16 17 21 26 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The LD50 values for complex 1 in HeLa cells are 0.2 μM with light and 1.6 μM without, giving a photo-index of 8. It is worth noting that while other compounds have been shown to have values of up to 3 magnitudes higher 22 23 , many other small metal complexes are reported with similar photo-indexes of <10 16 17 21 26 .…”
Section: Discussionmentioning
confidence: 97%
“…In several cancer cell models complex 1 has been demonstrated to behave as a promising photosensitizer under visible light (405 nm light, light dose 3.6 J cm −2 ). The typical light dose range used in PDT with small metal complexes is ~2–30 J cm −2 , demonstrating that complex 1 -induced photosensitizion can be caused by comparatively low doses of light 13 16 21 22 23 24 26 . The LD50 values for complex 1 in HeLa cells are 0.2 μM with light and 1.6 μM without, giving a photo-index of 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same team published another diamagnetic Fe( ii ) complex bearing ligands, which induces apoptosis in cancer cells with significant phototoxicity under visible light irradiation ( Fe-2 ). 76 A new type of Fe( ii ) complex was presented in 2018 by Tabrizi: it bears a tridentate ligand (which stabilizes the ferrous state as a pincer) appended with a BODIPY moiety known for its mitochondria-targeting, photodynamic and emissive properties ( Fe-3 ). 77 The complex displays good cytotoxicity upon 500 nm irradiation (1.06 μM in HeLa cells) while remaining essentially non-toxic in the dark.…”
Section: Phototoxic First-row Transition Metal Complexesmentioning
confidence: 99%
“…A recent study has also demonstrated the use of pyridyldipyridophenazine substituted Fe(II) complexes as partial DNA intercalative binders. The complexes had phototoxicity upon visible light irradiation, in addition to a low dark toxicity [53]. Inspired from the works described above, we have decided to investigate the potential of Fe(II) polypyridyl complexes as chemotherapeutic agents and PDT PSs.…”
Section: Introductionmentioning
confidence: 99%